Changing task contents of jobs in India: Implications and way forward - Pankaj Vashisht; Jay Dev Dubey (Indian Council for Research on International Economic Relations (ICRIER), 2018)
In this paper, we analyse the evolution of the task content of jobs in India between 1983 and 2011. Following standard literature, we calculated five task intensities by combining NSS data with O-Net data at the 3-digit level of occupational classification. We find that, in line with global trend, non-routine cognitive analytical as well as non-routine cognitive interactive task intensity of jobs has increased in India, while manual task intensities have declined. However, unlike in the US and Europe, the routine cognitive task content has not declined. Our analysis further shows that technology seems to be a major factor behind the evolution of non-routine cognitive analytical and interactive tasks in India whereas structural change and change in the supply of labour has shaped manual task contents.
Keywords: J23; J24; I25; 330; Task content of jobs; routinisation; job polarisation